Beyond the Brain How the Mind and the Body Shape Each Other - Fei, Duoyi (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
Different from traditional research on the mind-body problem often discussed from an epistemological viewpoint, which assumes that mental processes are internal to the person, this book demonstrates the crucial role of contextual relevance in the workings of the mind and illustrates how mind emerges from the individual's interactions with her physical, social, and cultural environments. It also develops the interpersonal and social aspects of embodied mind. The body that creates meaning is not only an emotional, kinesthetic, and aesthetically experiencing body; the body that creates meaning is a social body. It suggests that mind-body relations are not only achieved through the interaction between our own mind and body, but by other minds in our intersubjective interactions. It is related to epistemology, metaphysics, ethics, value theory, action theory, and the philosophies of mind, science, logic, and technology. The readership may include graduate and undergraduate students studying philosophy, law, political science, sociology, psychology, etc., educators, researchers, scholars, and anyone who shows an interest in philosophy.
Chapter 1. Introduction -- Chapter 2. The Conceptual Fetters of the Mind-body Problem -- Chapter 3. From 'the Mind Isolated with the Body' to 'the Mind Being Embodied' -- Chapter 4. In What Sense Should We Talk about the Perception of Other Minds? -- Chapter 5. Comparative Perspectives on Solutions for the Problem of Other Minds -- Chapter 6. The Justification of Knowledge and the Limits of Mind -- Chapter 7. What Makes Consciousness 'Conscious'? -- Chapter 8. Social Shaping of Emotion.
Keywords: Knowledge, Theory of; Philosophy of mind; Science -- Philosophy; Epistemology; Philosophy of Mind; Philosophy of Science